Selected Leadership Factors as Self-Assessed by Entrepreneurs with Gender Perspective: An Empirical Research from Slovakia - Lucia ZBIHLEJOVA; Zuzana BIRKNEROVA (Communications of International Proceedings, 2024)
Years of studies have proven that while human potential should not be measured in terms of sex or gender differences, the work performance should – as evidenced by science. The presented paper is therefore aimed to observe the possible gender differences in the selected leadership styles of entrepreneurs. It brings about an assumption that there are statistically significant gender differences in the self-assessment of the paternalistic leadership style attributes between the addressed male and female entrepreneurs. The research sample consisted of 315 entrepreneurs, of which 180 (57.1%) were women and 135 (42.9%) were men. Gender differences between the selected attributes of paternalistic leadership style of entrepreneurs were analyzed by the original PL28 methodology. For identification of these differences, Student's t-test for two independent samples was used and calculated in the IBM SPSS 26 software. The research results prove that there are several statistically significant gender differences recorded within the PL28 factors of Lenient, Authoritarian and Moral leading.
Keywords: leadership styles; gender differences; entrepreneurs